In House Training Penyusunan Modul Ajar Project Penguatan Profil Pelajar Pancasila (5P) SMA ITCI Kelurahan Kenangan Kecamatan Sepaku Kabupaten Penajam Paser Utara - Casmudi Casmudi; Kiftian Hady Prasetya; Sugianto Sugianto; Ririn Suyanti (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
Community Service Activities (PkM) aim to synergize the Tri Dharma of Higher Education with ITCI High School partners in North Penajam Paser Regency. PkM provides services in the form of In House Training (IHT) for teachers in compiling teaching modules of the Pancasila Student Profile Strengthening Project (5-P) for Teachers. PkM assistance was carried out for 2 days for 16 hours. The IHT activity was preceded by an opening ceremony by the school principal and supervising supervisor from the East Kalimantan Kemdikbud regional office representing the south. The PkM target is all ITCI SMA teachers totaling 22 people. IHT agenda is in the form of presentation of the basic philosophical, theoretical, psychological and rational foundations of 21st century learning. The delivery of teaching module guidance material focuses on operational techniques for compiling project learning teaching modules (5-P), PkM activities are supported by collecting data using questionnaires about aspects knowledge, confidence in being able to carry out project based learning, overcome obstacles, and recognize changes in students' digitalization learning literacy. The results showed that the knowledge of teachers participating in IHT, 1) The teacher's understanding of the concept of PJBL achieved an average score of 92% 2) Confidence about the ability to implement PJBL obtained an average score of 89.5%. 3) recognizing obstacles in the implementation of PJBL obtained a score of 92% of 4) recognizing changes in students' digital literacy behavior obtained a score of 95.67%.